2013
DOI: 10.1155/2013/518094
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Inflammation-Induced Bone Damage in Arthritis and Their Control by Herbal Products

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation of the synovial joints leading to bone and cartilage damage. Untreated inflammatory arthritis can result in severe deformities and disability. The use of anti-inflammatory agents and biologics has been the mainstay of treatment of RA. However, the prolonged use of such agents may lead to severe adverse reactions. In addition, many of these drugs are quite expensive. These limitations have necessitated the search for newer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 140 publications
2
27
0
Order By: Relevance
“…Recent in vitro and in vivo studies have shown that polyphenols down-regulate pro-inflammatory cytokines, stimulate anti-inflammatory agents, increase forkhead box P3 (Foxp3)-expression in CD4+ regulatory T-cells, and prevent bone loss [56]. In the following, we review the promising application of several polyphenols in studies aimed at modulation of inflammation.…”
Section: Natural Anti-inflammatory Compounds To Modulate Inflammatmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent in vitro and in vivo studies have shown that polyphenols down-regulate pro-inflammatory cytokines, stimulate anti-inflammatory agents, increase forkhead box P3 (Foxp3)-expression in CD4+ regulatory T-cells, and prevent bone loss [56]. In the following, we review the promising application of several polyphenols in studies aimed at modulation of inflammation.…”
Section: Natural Anti-inflammatory Compounds To Modulate Inflammatmentioning
confidence: 99%
“…They are most famous for their antioxidant, anti-inflammatory, and anti-carcinogenic properties [56, 117]. In the following, we provide a review of four promising flavonoids with potential to mediate inflammatory response to biomaterials.…”
Section: Natural Anti-inflammatory Compounds To Modulate Inflammatmentioning
confidence: 99%
See 1 more Smart Citation
“…[60] Tripahala is an Ayurvedic herbal formulation that shows antiarthritic effect in adjuvant-induced arthritis in mice. Its oral treatment restores levels of lysosomal enzymes, tissue marker enzymes, glycoproteins and paw thickness in adjuvant-induced arthritic animals.…”
Section: Triphalamentioning
confidence: 99%
“…As an effective defense in biology, the inflammatory response usually lacks specificity and overreacts to cause significant bystander damage which activated in response to pathogens or tissue damage and amplified the inflammatory response to induce production of inflammatory mediators including nitric oxide, reactive oxygen species, proinflammatory cytokine s (such as IL-1, NFκB, AP-1, IL-6, IL-17, IL-18, TGFβ, and TNFα), chemokines (MMPs, MCP-1) and prostaglandins, associated with vicious circle of cell death, and so on [1,2].…”
Section: Introductionmentioning
confidence: 99%